Design and development of an adhesive antenna - Tan, Eileen Mei Foong (2019)
Due to the advancement of technology, the quality of life of mankind has been improving. One of the most essential factors which mediate a better and more comfortable living standard is the rapid development of wireless communication. Wireless communications have contributed significantly in the technological advancement in the healthcare and medical fields. This project presents the design of a 24 mm × 24 mm × 1 mm adhesive antenna which is used specifically for biotelemetry. The antenna is fabricated on a Rogers RT/duroid 5880 dielectric substrate. The antenna is designed using High Frequency Structure Simulator (HFSS). The antenna acts as a gateway between implantable medical devices and the external base station. It allows the implanted devices to communicate with the base station via the Wireless Body Area Networks (WBANs). The proposed planar monopole adhesive antenna is capable of operating in three resonant bands. The adhesive antenna resonates at the ISM (2.4 – 2.5 GHz), WBAN (3.1 – 10.6 GHz) and WLAN (5.15 -5.725 GHz) bands. The designed antenna is simulated using HFSS and the fabricated antenna is experimentally verified by attaching it onto a human’s skin. Furthermore, the gain of the antenna is above -13.57 dBi, whereas the average SAR values at 2.41 GHz, 3.27 GHz and 5.06 GHz are respectively, below 3.217 μW/kg, 7.035 μW/kg and 27.85 μW/kg. Average SAR is known as Specific Absorption Rate to measure the rate of energy absorbed by the human body when exposed to an electromagnetic field of radio frequency. The designed antenna is safe to be used by the users as the average SAR values for the antenna are below the limits set by the IEEE C95.1-1999 and IEEE C95.1-2005 standards. The antenna’s simulation and measurement performances confirm its omnidirectional radiation patterns and good tri-band operations with high reflection coefficient.